Approximate controllability of impulsive semilinear evolution equations in Hilbert spaces - Asadzade, Javad A.; Mahmudov, Nazim I. (Taylor & Francis Ltd, 2025)
Several dynamical systems in fields such as engineering, chemistry, biology, and physics show impulsive behaviour by reason of unexpected changes at specific times. These behaviours are described by differential systems under impulse effects. The current paper examines approximate controllability for semi-linear impulsive differential and neutral differential equations in Hilbert spaces. By applying a fixed-point method and semigroup theory, a new sufficient condition is provided for the ( $ \mathcal {A} $ A-controllability) approximate controllability of neutral and impulsive differential equations (IDEs). To demonstrate the value of the suggested consequences, three examples are presented, offering improvements over some recent findings.
Keywords: Approximate controllability; existence and uniqueness; impulsive systems